1997
DOI: 10.1016/s0255-2701(97)00017-2
|View full text |Cite
|
Sign up to set email alerts
|

Hot gas filtration, using a moving bed heat exchanger-filter (MHEF)

Abstract: A study was conducted on the use of a Moving Bed Heat Exchanger-Filter (MHEF) for removing fine dust particles from gases. The influence of a number of variables was examined, including gas velocities, solid velocities, gas temperatures and dust sizes. The collection efficiency was found to decrease with increasing temperature; the total collection efficiency decreases strongly when the solid velocity increases. A stable numerical model for filtration and heat exchange was developed that predicts the two dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…The cross-flow MBHEF concept for tar and particulate removal would provide a high contact area between gas and solids without either entrainment or elutriation of solids. Furthermore, to date, MBHEF systems have only been designed for heat transfer and hot gas particulate removal: to be optimised from an energy and exergy point of view [15]; to propose a modelling approach to predict dust filtration with the gas temperature and the dust particle diameter [31] or with the solid velocity [32]; to be improved by the analysis of their design, strong features and drawbacks and to point out their performance according to a patent review [33]; to study the feasibility of using Lapilli as granular medium [34]. Dealing with BFBG reactors, MBHEF systems could also act as a preheater of the gasifying agent as the exhaust gas is cooled down and conditioned to be used for power production in ICE's, GT's, etc (Fig.…”
Section: Contaminantmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-flow MBHEF concept for tar and particulate removal would provide a high contact area between gas and solids without either entrainment or elutriation of solids. Furthermore, to date, MBHEF systems have only been designed for heat transfer and hot gas particulate removal: to be optimised from an energy and exergy point of view [15]; to propose a modelling approach to predict dust filtration with the gas temperature and the dust particle diameter [31] or with the solid velocity [32]; to be improved by the analysis of their design, strong features and drawbacks and to point out their performance according to a patent review [33]; to study the feasibility of using Lapilli as granular medium [34]. Dealing with BFBG reactors, MBHEF systems could also act as a preheater of the gasifying agent as the exhaust gas is cooled down and conditioned to be used for power production in ICE's, GT's, etc (Fig.…”
Section: Contaminantmentioning
confidence: 99%
“…Dirty bed particles can be cleaned by vibration [32], recirculated to the moving bed filter if the dust and tar concentration are not too high or used as inert material in a fluidized bed if the gasification is carried out in such equipment.…”
Section: Filtration Modelmentioning
confidence: 99%
“…They also showed that the particle velocity at the walls is 25% below the velocity in the plug flow region for fully rough walls. Zou and Yu [22] showed, for both loose Table 1 Experimental data of the work of Henriquez and Macías-Machín [9]. Variables that are subject to variations throughout the paper are in bold format and capital letters.…”
Section: Governing Equationsmentioning
confidence: 99%
“…For high temperature heat exchange and filtration, alumina and silica sand (with a size ranging between 0.5 and 2.0 mm) are typically used in industrial applications [13,17]. Spheres of steel are also widely used [6,9]. Recently, Macias Machin et al [18] presented "lapilly", a new material for gas filtration applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation